Scrotal doppler ultrasound evaluation in Zaria, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:The superficial location of the scrotal contents makes them ideally suited for sonographic examination. The development of high-frequency, real-time greyscale scanners along with Doppler facility has enhanced the diagnostic accuracy of scrotal sonographic examinations.Objectives:To determine the pattern and utility of Doppler ultrasound in the assessment of patients with scrotal pathologies in Zaria, Nigeria.Methodology:This retrospective study was carried out over a period of 36 months (February 2012 to January 2015) at the Radiology Department of Ahmadu Bello University Teaching Hospital, Zaria, Nigeria, on patients who presented for scrotal sonography on account of scrotal pathology. After a brief examination, colour Doppler ultrasound scan (CDUS) was performed. The clinical diagnosis and final ultrasound diagnosis were compared to determine the sensitivity and specificity of the later.Results:A total of 115 patients were scanned. Nearly 55.6% presented on account of primary infertility. Varicocele (45), hydrocele (31), epididymo-orchitis (8), epididymal cyst (6), microlithiasis (6) and others (6) were frequent Doppler findings. Only 12 cases were normal scan. Overall sensitivity of CDUS in diagnosing varicocele and hydrocele was 100% each, respectively.Conclusion:Doppler ultrasonography is an excellent, safe and reliable method for evaluating patients with scrotal diseases. It is especially important in conditions such as varicocele and hydrocele where accurate diagnosis is required in the management of infertility.